Legal Certainty of Supervision of Digital Gold Business for Electronic Money Providers in The System Risk-Based Business Licensing - Ananda Putra Herdinansyah; Nunik Nurhayati (Universitas Muhammadiyah Surakarta, 2026)
Indonesia is a developing country, particularly in the payment systems and digital gold commodity futures trading sectors, where digital platforms combine these two types of businesses. This raises the potential for overlapping supervisory authority between Bank Indonesia and Bappebti and creates legal uncertainty. This study aims (1) to determine and analyze how the supervision of digital gold businesses for electronic money providers is regulated in a risk-based business licensing system; (2) to examine and analyze whether this supervision has fulfilled the principles of legal certainty and clarity of authority from a state administrative law perspective. This research is normative research with a statutory approach method. This study brings innovation by examining providers of electronic money and digital gold in one platform. The main focus is to ensure legal certainty to overcome overlapping authority between Bank Indonesia and Bappebti, by harmonizing the OSS-RBA system. Supervision of electronic money payment systems in Indonesia has been clearly regulated by Bank Indonesia. The regulations are contained in Law No. 23/1999 because Law No. 6/2009. Supervision of digital gold commodity trading is carried out by Bappebti. This is based on Law No. 10/2011. The government currently uses a risk-based business licensing system (OSS-RBA), regulated by Government Regulation No. 28/2025. The merger of electronic money and digital gold trading businesses into oneplatformThis creates legal uncertainty and the potential for overlapping supervisory authority. The government needs to formulate regulations that clearly define the boundaries of responsibility and how to resolve disputes across these sectors. The OSS-RBA system must be utilized comprehensively, not only as a platform for processing permits but also as an integrated supervision database.